Analysis of CSR Activities in the DHL Company - Hošová, Kateřina; Pošvicová, Zdena, 1951-; Kozáková, Soňa; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2017)
This diploma thesis focuses on Corporate Social Responsibility: a phenomenon which is gaining importance, especially in connection with the ongoing boom and the growing impact of transnational corporations in the world. The thesis is divided into two main parts and contains seven chapters in total. First three chapters summarise a theoretical framework of the CSR matter, different ways of reporting the results and the influence of transnational corporations in the world. The following chapters concern evaluation of corporate responsibility and its realisation in a transnational company DHL. Firstly, the company is briefly introduced and framework strategies and goals in the CSR area are mentioned, mainly on the corporate level. The next part focuses directly on the description of key activities in detail and their development particularly via so-called corporate citizenship. Lastly, the main differences in the corporate citizenship area between different regions, where DHL operates, are introduced, namely Europe, Asia and Pacific, and the Americas. As a basis for the analysis was used a survey held among employees of the company in different regions, aimed at their own perception of the CSR matter and its particular implementation within the company. The analysis of the survey is included in a separate chapter of the thesis.
Vedoucí práce: Zdena Pošvicová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses